GENDER AND OTHER INFLUENCES ON WATER TRANSPORTATION SERVICE PROVISION ON THE OGUTA LAKE, IMO STATE, NIGERIA - Azuwike, Okechi Dominic; Eboh, Emmanuel (African Journal of Social and Behavioural Sciences, 2019)
This study on Gender and other Influences on Water Transportation Service Provision on the Oguta Lake, Imo State, Nigeria, assesses sustainability of the transport mode that prominently features wooden boats against the background of gender expressed in competition for ferry service enterprise on the Oguta Lake. It is focused on finding out the market share of commercial water activities on the Oguta Lake held by women; reasons for identified level of women.s role in the industry; market share held by various water crafts; strength of women in the enterprise over the years; and profiling of ferry service women in the context of change. The investigation took place around the Oguta Lake in Imo State in the course of three months between August and October 2016. A total of 10 women canoe operators and 46 passengers were interviewed. Observation station was mounted at the embarkation/disembarkation point on the Oguta II end of the lake. Results show diurnal dominance of women in the commercial (passenger/goods) canoe mode at 71.8 percent and this dominance is held by 100 percent of respondents to be of a cultural/traditional motivation. Among crafts in operation, canoe is also dominant, not only in number of units but also in number of passengers ferried per day. In the face of increased affordability of speed boats, the canoe women and their enterprise are of questionable sustainability in terms of competitiveness.